'Life as literature': Wright Morris's Love Among the Cannibals. Issue 3 (4th March 2023) - Kochin, Michael S.
ABSTRACT: To become oneself, one must gain ownership of one's language and authorship of the stories one tells. The partisans of vitalism, and the prophets of a new American literature, both claim that the way to own one's language is to seek out new experiences that have not yet been put into language and put them into a language of one's own. Morris's alternative, set out in his critical writings but most fully exemplified in his 1957 novel Love Among the Cannibals, is to appropriate what has already been written as literature in order to overcome the domination of cliché, what 'everyone' or 'every American' says and therefore thinks and does, over one's language, imagination, and experiences. Wright Morris is urgent for us if we are to escape faddish memes and cannibalise our memories and our reading to nourish our own imaginations, without which we cannot read or write ourselves into a better or more just future.